Use of dementia and caregiving-related internet resources by informal caregivers: A cross-sectional study - Teles, Soraia; Paúl, Constança; Costa-Santos, Cristina; Ferreira, Ana (Frontiers in Medicine, 2022)
Informal dementia caregivers are at greater risk of experiencing physical and mental health issues as compared to the general population. Internet-based resources may provide accessible opportunities to backing informal dementia caregivers by addressing their information and support needs. This cross-sectional study aims to characterize the use of dementia and caregiving-related internet resources by caregivers and identify variables associated with such use. Primary data were collected through a web-based survey (N=158). Linear regression models were used to assess the associations of predisposing, enabling, and need variables with the frequency of using the internet for caregiving-related purposes. Most caregivers (93%) have ever used the internet to gather general information about dementia. The frequency of using internet resources was, however, moderate. The multivariable linear regression model suggests that being younger (β=-.110, p=.009), not having a source of support to provide care (β=-.2.554, p=.012), having used a face-to-face psychosocial intervention at some point (β=2.731, p=.003), being employed (β=2.558, p=.013), and appraising one’s own physical health negatively (vs. appraising it as similar; β=3.591, p<.001), are associated with a higher frequency of using caregiving-related internet resources. Our findings confirmed the association of age and perceived health status with caregiving-related internet use reported in other studies. The role of enabling variables as lifetime access to psychosocial interventions and having a usual source of support to provide care was a new addition. This study informs the design and deployment of information and support to dementia caregivers.